Life in the studio : inspiration and lessons on creativity - Palmer, Frances (Potter) (Artisan, 2020)
"To step into potter Frances Palmer's world is to be surrounded by the trappings of a life that has been intentionally-and painstakingly-built to maximize creativity. A light-filled, airy studio in which to make her pottery, with a corner always at the ready for her daily photo shoots. Cutting gardens overflowing with flowers to be snipped as inspiration strikes. Shelves of cookbooks to peruse as she plans the menu of her next dinner party, and museum catalogs and art books to pore over when it's time to imagine a new vessel. After 30 years as an artist and entrepreneur, Palmer has learned how to cultivate a life that brings out her best. Those years have been at once rewarding and challenging, fruitful and fraught, and through it all, she has discovered the things that matter most: determination, routine, prioritization, perseverance, and perspective. She has distilled these hard-won lessons, and more, into her debut book, a manual for current and aspiring creatives. The book is loosely arranged chronologically, beginning with Palmer's background in art history and the foundations of her pottery practice through to the day-to-day of running her successful business and tending to her ever-evolving gardens, and culminating in the continuous exploration and collaboration she is engaged in today. Along the way, readers are brought behind the scenes with hundreds of gorgeous photographs (of her ceramics, her beautiful flower arrangements, her gardens, and more), and even step-by-step instructions for her most cherished techniques and recipes. It all adds up to a one-of-a-kind portrait and handbook for a creative life, well-lived"--